Total Phenol Content, Total Flavonoid Content, Antioxidant Activity and GC-MS Analysis of a New Variety of Rice (Oryza sativa L.) - Hafidha Asni Akmalia; Dwimei Ayudewandari Pranatami (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Consuming foods rich in antioxidants plays an important role in human health, one of which is through rice. This research aimed to describe the total phenol content and total flavonoids content as well as GC-MS analysis of raw Baroma rice extract and analyze the antioxidant activity of Baroma rice in different cooking methods. Baroma rice was collected from Semarang, Central Java, Indonesia thus was analyzed to get data about total phenol content, total flavonoid content, and compouds identifies using GC-MS. We also analyzed antioxidant activity of Baroma rice among raw, rice cooked in stove and magic com extract using Anova test followed by Tukey test. The result proved that total phenol content was 85.64 mg/L and total flavonoid content was 78.28 mg/L, meanwhile the highest antioxidant activity was in raw extract of Baroma followed by rice cooked in magic com and stove, suggesting that cooking method effected on its property. GC-MS analysis showed the diversity of chemical compound, totaling 15 compounds and peaks.